2010
DOI: 10.1590/s1413-35552010000300007
|View full text |Cite
|
Sign up to set email alerts
|

Efetividade do treinamento de resistência à fadiga dos músculos dos membros inferiores dentro e fora d'água no equilíbrio estático e dinâmico de idosos

Abstract: Background: Aging compromises the ability of the central nervous system to maintain body balance and reduces the capacity for

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
35

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 26 publications
2
11
0
35
Order By: Relevance
“…We also verified a significant decrease in both SBP and DBP, with the continuous group showing greater values for DBP throughout the intervention period. The improvement in body balance can be explained by the instability created by the aquatic environment, mainly in the DWR modality, in which the subjects do not have contact with the bottom of the pool (Melzer et al 2008;Avelar et al 2010). The results of the present study are in accordance with the findings of other studies in the literature on older adults: Kaneda et al (2008) reported a reduction of 14 % in the execution time of the tandem gait.…”
Section: Discussionsupporting
confidence: 90%
“…We also verified a significant decrease in both SBP and DBP, with the continuous group showing greater values for DBP throughout the intervention period. The improvement in body balance can be explained by the instability created by the aquatic environment, mainly in the DWR modality, in which the subjects do not have contact with the bottom of the pool (Melzer et al 2008;Avelar et al 2010). The results of the present study are in accordance with the findings of other studies in the literature on older adults: Kaneda et al (2008) reported a reduction of 14 % in the execution time of the tandem gait.…”
Section: Discussionsupporting
confidence: 90%
“…Durante a reavaliação da marcha com movimentos verticais da cabeça, foi verificada melhora significativa na execução de rotações uniformes da cabeça sem nenhuma mudança na marcha, o que pode ser explicado por uma melhora da força muscular e da reação dos músculos agonistas, facilitando, dessa forma, a mudança na direção dos movimentos, bem como uma maior coordenação destes 20 .…”
Section: Resultsunclassified
“…Pode-se inferir ainda que a propriedade de suporte que é conferida pela água possibilita a realização de atividades mais independentes por parte de indivíduos com alteração do equilíbrio corporal, proporcionando, assim, maior tempo de reação para se equilibrar 20,22 .…”
Section: Resultsunclassified
“…Outro estudo similar ao de Resende et al (2008) foi o de Avelar et al (2010), no qual participaram 46 idosos, acima de 60 anos, divididos aleatoriamente em três grupos. O primeiro grupo realizou atividades de resistência muscular no meio aquático (fisioterapia aquática), o segundo grupo realizou as mesmas atividades em ambiente terrestre e um terceiro grupo não realizou atividade alguma (grupo controle).…”
Section: Resultados E Discussõesunclassified